2019
DOI: 10.3390/ph12020081
|View full text |Cite
|
Sign up to set email alerts
|

Cardiolipin-Based Lipopolyplex Platform for the Delivery of Diverse Nucleic Acids into Gram-Negative Bacteria

Abstract: Antibiotic resistance is a growing public health concern. Because only a few novel classes of antibiotics have been developed in the last 40 years, such as the class of oxazolidinones, new antibacterial strategies are urgently needed (Coates, A.R. et al., 2011). Nucleic acid-based antibiotics are a new type of antimicrobials. However, free nucleic acids cannot spontaneously cross the bacterial cell wall and membrane; consequently, their intracellular delivery into bacteria needs to be assisted. Here, we introd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…With the rapid development of DNA nanotechnology, a variety of self-assembled DNA nanomaterial with different sizes and spatial structures have been developed. The list of applications of DNA nanostructure research is endless in the field of molecular biology, including the use of these nanomaterials as -biosensors, vehicles, for drug delivery, and so on [ [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] ]. At present, the antibacterial application of DNA nanostructures mainly focused on optimizing bactericidal performance and cytotoxicity by combining these nanostructures with other antibacterial substances [ [38] , [39] , [40] , [41] ].…”
Section: Discussionmentioning
confidence: 99%
“…With the rapid development of DNA nanotechnology, a variety of self-assembled DNA nanomaterial with different sizes and spatial structures have been developed. The list of applications of DNA nanostructure research is endless in the field of molecular biology, including the use of these nanomaterials as -biosensors, vehicles, for drug delivery, and so on [ [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] ]. At present, the antibacterial application of DNA nanostructures mainly focused on optimizing bactericidal performance and cytotoxicity by combining these nanostructures with other antibacterial substances [ [38] , [39] , [40] , [41] ].…”
Section: Discussionmentioning
confidence: 99%
“…Third, Ji-Hyun Yeom et al utilized NAM with an antimicrobial peptide to improve the penetrative ability of the antimicrobial peptide . Fourthly, the combination of NAM and metal nanoparticles can reduce the cytotoxicity of metal nanoparticles and maintain its killing effect. , Finally, NAM combined with traditional antibiotics enhances antibiotic efficacy and reduces the requirement for high doses of antibiotics. Nanomedicines have been widely studied and used as antibacterial choice. , DNA nanostructures, used alone or functionalized with specific DNA sequences, are used as an antimicrobial therapy for severe bacterial infection. , Tetrahedral framework nucleic acids (tFNAs) are self-assembled by four single-stranded DNA (ssDNA) molecules via highly specific base pairing. Our previous studies showed that tFNAs have excellent biocompatibility and inherent nontoxicity to bacterial and mammalian cells. The size and structure of tFNAs can be accurately regulated; thus, it is a suitable therapeutic delivery vehicle to deliver antitumor drugs to tumor cells and restore the sensitivity of chemotherapy drugs . Moreover, tFNAs could transfer antisense peptide nucleic acids to drug-resistant bacteria and enhance its bactericidal effect …”
Section: Introductionmentioning
confidence: 99%
“…Several essential genes such as the gyrA , ftsZ , and acpP have already been recognized as potential targets for antimicrobial ASOs. 11 , 16 , 18 , 24 , 29 , 30 , 31 , 32 , 33 , 34 , 35 Despite being prevalent in a wide range of both Gram-negative and Gram-positive pathogens, 11 , 16 , 17 , 18 , 24 , 26 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 the presence of mutations in these genes can pose challenges in designing broad-spectrum ASOs. However, they still serve as suitable targets for narrow-spectrum ASOs.…”
Section: Asosmentioning
confidence: 99%
“… E. coli ; P. aeruginosa Perche et al. 42 EPC/DMPG/PEG2000-DSPE liposomes (molar ratio: 14:0.9:1) loaded with PS/DNA-PEI complexes (N/P ratio: 8) MIC: 3 μg/mL (0.5 μM) Resistance gene inhibition: 100 μg/mL (17.4 μM) N.A. MDR– P. aeruginosa Wang et al.…”
Section: Intracellular Delivery Of Charge-neutral Asosmentioning
confidence: 99%